The relationship between science and religion in Kang Youwei’s Confucianism - Wan, Z (2019)
In this thesis I analyse the relationship between science and religion in a non-Western and specifically Chinese context through an examination of the writings of Kang Youwei (康有爲1858–1927), a prominent reformer and Confucian thinker of the period of transition from Imperial to Republican China. Described by his followers as the ‘Martin Luther of Confucianism’, Kang envisioned a central social role for Confucianism as a state religion, championing the restoration of a ‘pristine’ religion of Confucius (Kongjiao孔教), by both modelling it after Christian practices and revitalizing the ancient Chinese belief in Shangdi 上帝 (as a universal concept, equated with ‘God’). He upheld the unitary nature of the concept of jiao (教) or ‘religion’, manifested in a variety of religions united by their shared moral aim and in their teachings on reverence for Divinity, the soul’s immortality, and compassion. My research reveals that, before the rise of radical materialism and scientism, fully one generation before the acceptance by Chinese intellectuals of the ‘Conflict Thesis’, Kang had already sought to conceptualize the relationship between what are now generally categorized as science and religion. Expounding a holistic world-view founded upon a belief in the oneness of knowledge, Kang appropriated Western scientific concepts such as the ‘ether’ in his re-interpretation of the Confucian Classics. He saw no conflict between modern science and Confucian Religion, whose quintessential doctrines, in his view, contained the origins of scientific thought. Acknowledging that conflict with science might occur with other religions like Christianity, he admitted that certain religious doctrines required correction when scientific evidence made it imperative; no matter how far science advanced, however, it could never disprove the existence of God, whose infinite nature he believed lay beyond the grasp of finite—even if brilliant—scientific minds. Closer analysis of Kang’s conception of the complementary relationship between science and religion, I suggest, can contribute to a richer picture of Kang’s thought, a better understanding of the field of science and religion in China, and a more global account of the subject.